2016
DOI: 10.1021/acs.est.6b03209
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Pb Pollution in Central East Antarctic Snow: A Retrospective Assessment of Sources and Control Policy Implications

Abstract: Well-defined variations in the enrichments and isotopic compositions of Pb have been observed in snow from Dome Fuji and Dome A in the central East Antarctic Plateau (EAP) over the past few decades. The Pb isotopic fingerprints indicate that the rapid increase in Pb enrichments from the mid-1970s, reaching a peak in ∼1980, is due to the massive use of leaded gasoline in northern South America, especially Brazil. Since then, they show a continuous decline, mostly due to the significant removal of the Pb additiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The EBC concentrations were similar to the EBC concentrations measured at coastal stations such as Halley and Neumayer (Wolff and Cahier, 1998;Weller et al, 2013). In contrast, EBC concentrations at Ferraz, Maitri, and Larsemann Hills were higher than those at Syowa (Pereira et al, 2006;Chaubey et al, 2010). Ferraz is located in the northern area of the Antarctic Peninsula as presented in Fig.…”
Section: Variations In Ebc At Syowa Station Antarcticamentioning
confidence: 88%
“…The EBC concentrations were similar to the EBC concentrations measured at coastal stations such as Halley and Neumayer (Wolff and Cahier, 1998;Weller et al, 2013). In contrast, EBC concentrations at Ferraz, Maitri, and Larsemann Hills were higher than those at Syowa (Pereira et al, 2006;Chaubey et al, 2010). Ferraz is located in the northern area of the Antarctic Peninsula as presented in Fig.…”
Section: Variations In Ebc At Syowa Station Antarcticamentioning
confidence: 88%
“…Finally, a shift in the geochemical data of the top two rows of the grid suggests that the top of Unit H1 might have been affected by modern contamination. For instance, car emissions from the nearby highway may have resulted in contamination with S, Zn, and Cu (Huisman et al, 1997;Chang et al, 2016). Other potential sources of contamination that should be considered are animal urine and feces, which can contain Cl, K 2 O, Zn, P 2 O 5 , and Cu (Prinsloo, 2007;Chase et al, 2012).…”
Section: Site Taphonomymentioning
confidence: 99%
“…After the ban on leaded gasoline in major countries of the Southern Hemisphere from New Zealand in 1996 to South Africa in 2006, the Pb concentrations in Antarctic snow decreased. Chilean copper smelter production was later identified as a major source of Pb pollution in Antarctica (Chang et al 2016). To trace the source region responsible for anthropogenic Pb reaching Victoria Land, we compared the isotopic data of the Hercules Névé snow samples spanning the period 2012-2015 with those of anthropogenic sources.…”
Section: Sources Of Anthropogenic Pb In Hercules Névé Snowmentioning
confidence: 99%
“…Fine particulate Pb pollutants can be transported over long distances through the atmosphere, even reaching Antarctica, which is the most remote area on Earth, and Antarctic surface snow responds to the changing deposition of anthropogenic Pb. Thus, Antarctic snow layers provide records of past changes in Pb deposition, which helps us understand the global nature of atmospheric Pb pollution and recent changes in response to efforts to reduce Pb emissions (Wolff and Suttie 1994, Barbante et al 1997, Planchon et al 2002, Chang et al 2016. A few reliable records have demonstrated that peak Pb pollution in Antarctica occurred in the 1970s and 1980s with a small time difference between the regions; the late 1970s-1980s in the Atlantic sector of Antarctica (Coats Land) Suttie 1994, Planchon et al 2003), the late 1980s in the Pacific sector (Victoria Land) (Barbante et al 1997, Van de Velde et al 2005, and the 1960s-1980s in the Indian sector (Law Dome) (Vallelonga et al 2002, Van de Velde et al 2005 (figure S1 (available online at stacks.iop.org/ERC/4/055006/mmedia)).…”
Section: Introductionmentioning
confidence: 99%